National Education Longitudinal Study: Base Year Through Fourth Follow-Up, 1988-2000 ([Verlag nicht ermittelbar], 2004)
This data collection presents base year through fourth follow-up data for the National Education Longitudinal Study (see NATIONAL EDUCATION LONGITUDINAL STUDY, 1988 [ICPSR 9389], FIRST FOLLOW-UP, 1990 [ICPSR 9859], SECOND FOLLOW-UP, 1992 [ICPSR 6448]), and THIRD FOLLOW-UP, 1994 [ICPSR 6961]. In addition, these data sustain continuing trend comparisons with NATIONAL LONGITUDINAL STUDY OF THE CLASS OF 1972 (ICPSR 8085) and HIGH SCHOOL AND BEYOND, 1980 (ICPSR 7896, 8297, 8443, 8896). NELS:88/2000 collected information on this cohort's accomplishments 12 years after the eighth-grade baseline survey. The 2000 data were collected at a key stage of life transitions for the eighth-grade class of 1988 since most had been out of high school for nearly eight years and many had already completed postsecondary education, started or even changed careers, and started families. Part 1, Student-Level Data, includes universe variables, base-year, first and second follow-up student components, school variables at the student level, second and third follow-up early graduate supplement and student-level transcript variables, first, second, and third follow-up dropout components, base-year and second follow-up parent components, and third and fourth follow-up questionnaires and derived variables. Part 2, Postsecondary Education Attendance Data, provides information for third and fourth follow-up respondents on attendance at postsecondary institutions. Part 3, Postsecondary Institution Data, supplies information about institutions applied to or attended by fourth follow-up respondents regarding sector, tuition/fee deciles, and enrollment. Part 4, Postsecondary 1994 Education Attendance Data, provides information for third follow-up respondents on attendance at postsecondary institutions, including enrollment dates and major fields of study.